The Rise of Centralistic Governance in Spatial Planning in Indonesia and Australia: A Comparative Study - Widiatedja, I Gusti Ngurah Parikesit; Qadam Shah, Mohammad; Sudiarawan, Kadek Agus; Yogantara, Pande (Administrative Law Departement Faculty of Law Universitas Sebelas Mare, 2023)
Since the Reformation, spatial planning governance has moved away from authoritarianism toward a more democratic style of government. However, the current Job Creation Regulation has heralded the return of the centralistic governance in spatial planning. Surprisingly, Australia is also experiencing this trend. This study will look at how the centralistic phase of spatial planning was implemented in Indonesia and Australia. By using a normative method, the results reveal that the spirit of centralization is obvious in the Job Creation Regulation. The central government has a dominating role in the implementation of spatial planning. It also controls the issuing of detailed plan. Because of the need to produce a digital map, the central government now has a power over the granting of spatial planning permission. In Australia, the local government evaluates and decides on the vast majority of planning applications. A countervailing tendency, nevertheless, has seen state governments take on some of the planning and decision-making duties once exercised by local governments. The state minister and development assessment panels are now responsible for authorization of significant projects. This pattern appears to depoliticize and simplify the application process for development projects, especially when those projects have financial advantages.